The The Impact of Changes in Workload and Subjective Well Being on Job Satisfaction through Work Motivation as a Mediator for Assistants for Persons with Disabilities at the Ministry of Social Affairs - Zonneveld, Tina (Indonesian Social Work Consortium (ISWC), 2022)
Since the formation of assistants with disabilities in 2018 to 2022, the number is significant, only a decrease of 13% from the initial total recruitment of companions. Employee job satisfaction is an important factor for employees to increase work motivation. This study aims to examine whether motivation and workload as well as subjective well-being affect the job satisfaction of assistants with disabilities in the Ministry of Social Affairs; To test whether subjective well being and workload affect job satisfaction through work motivation as a mediator fit with empirical data on assistants with disabilities at the Ministry of Social Affairs. This research uses quantitative with descriptive type. An online survey through google form was used with a sample of assistants with disabilities who met the criteria set by disability researchers at the Ministry of Social Affairs and spread across 34 provinces totaling 140. The results showed that there was a direct influence of workload and subjective will be on job satisfaction. The results of the path analysis of workload and subjective will being on job satisfaction through work motivation show that there is a significant effect.